ENERGY EFFICIENCY: BENEFITS FOR THE ECONOMY AND THE ENVIRONMENT (Eureka Journal of Business, Economics & Innovation Studies, 2026)
The article examines energy efficiency as one of the key factors of sustainable economic development and the reduction of negative environmental impacts. Particular attention is paid to environmental effects manifested in the reduction of pollutant emissions and the rational use of natural resources. The main directions for the implementation of energy-efficient technologies across economic sectors are analyzed, as well as the role of public policy in stimulating these processes. The study concludes that energy efficiency is a significant instrument for achieving a balance between economic growth and environmental safety.
Keywords: Energy efficiency, energy conservation, sustainable development, environmental safety, emission reduction, rational use of resources, “green” technologies.